Epigenetic factors Polycomb (Pc) and Suppressor of zeste (Su(z)2) negatively regulate longevity in Drosophila melanogaster. - Dasari, V.; Srivastava, S.; Khan, S.; Mishra, R.K. (Biogerontology, 2018)
The process of aging is a hallmark of the natural life span of all organisms and individuals within a population show variability in the measures of age related performance. Longevity and the rate of aging are influenced by several factors such as genetics, nutrition, stress, and environment. Many studies have focused on the genes that impact aging and there is increasing evidence that epigenetic factors regulate these genes to control life span. Polycomb (PcG) and trithorax (trxG) protein complexes maintain the expression profiles of developmentally important genes and regulate many cellular processes. Here, we report that mutations of PcG and trxG members affect the process of aging in Drosophila melanogaster, with perturbations mostly associated with retardation in aging. We find that mutations in polycomb repressive complex (PRC1) components Pc and Su(z)2 increase fly survival. Using an inducible UAS-GAL4 system, we show that this effect is tissue-specific; knockdown in fat body, but not in muscle or brain tissues, enhances life span. We hypothesize that these two proteins influence life span via pathways independent of their PRC1 functions, with distinct effects on response to oxidative stress. Our observations highlight the role of global epigenetic regulators in determining life span.